When style obscures substance: Visual attention to display appropriateness in the 2012 presidential debates. Issue 3 (2nd July 2016) - Gong, Zijian Harrison; Bucy, Erik P.
ABSTRACT: As with the first televised debates in 1960, the 2012 US presidential debates accentuated the importance of nonverbal behavior in political competition, with President Obama receiving widespread criticism for his disengaged and arguably inappropriate communication style in the first debate. To investigate the perceptual impact of such nonverbal expectancy violations, this study first employs an experimental design to examine the consequence of inappropriate leader displays, operationalized as nonverbal behaviors that are incongruent with the rhetorical setting. Theoretical explanations about the evaluative consequences of inappropriate leader displays are described in light of expectancy violations theory. Results of a repeated measures eye-tracking experiment find support for the prediction that inappropriate facial expressions increase visual attention on the source of violation, prompt critical scrutiny, and elicit negative evaluations. These findings are further explored with qualitative analysis of focus group responses to key moments from the first and third presidential debates. The discussion considers the broader implications of nonverbal communication in politics and how expressive leader displays serve as meaningful cues for citizens when making sense of televised political encounters.